A STUDY OF THE FACTORS RELATED TO PURCHASE INTENTION OF COSMETICS CUSTOMERS IN THAILAND - Taghipour, Amirhossein; Loh, Aaron (PEOPLE: International Journal of Social Sciences, 2017)
This research strives to examine the factors that are related to the purchase intention of Thai female customers toward Thai cosmetics in Bangkok, Specifically, it focuses on Srichand, one of the most renowned local Thai cosmetic brand in Thailand, with high sales revenues. A total of 30 current customers were interviewed to collect data. The results were analyzed utilizing the descriptive and inferential statistics. The results illustrate that most of interviewees stated that this Thai brand has some features such as affordability, availability even in local grocery shops, good quality in terms of smoothness, strength of whitening, goodness in removing the facial acne, and more importantly the positivity of customer’s perception on the ingredients of Srichand brand which contains herbal substances. These all factors are related to purchase intention of Thai female customers. This study will be helpful to Thai local cosmetic manufacturers to have a better understanding of their consumers’ behavior.